2011
DOI: 10.1002/cae.20298
|View full text |Cite
|
Sign up to set email alerts
|

A novel web‐based laboratory for DC motor experiments

Abstract: This article introduces a novel web-based DC motor laboratory, called NeTRe-LAB, to support teaching electrical machines. The NeTRe-LAB includes favorable animations to facilitate understanding characteristics of the DC motor, interactive DC motor models for instructive simulations, and web-based experiments with online monitoring features. To illustrate the current operations, remote access to an experimental setup of a DC motor has been provided and the speed control of it has been realized over Internet. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 118 publications
(157 reference statements)
1
27
0
1
Order By: Relevance
“…Basilio and Matos [7] proposed new tuning methods for proportional-integral (PI) and PID controllers that need only parameters obtained from the plant step response, the hardware implementation is not presented. Other works present web-based solution, for example, Colak et al [8] developed an advanced learning laboratory (NeTRed-LAB) for a DC motor that will allow students to operate real-world experiment on Internet. Albino-Mendez et al developed a free control Web-based tool; the tool covered basic and advanced operations allowing to work with both continuous and discrete-time system.…”
Section: Introductionmentioning
confidence: 98%
“…Basilio and Matos [7] proposed new tuning methods for proportional-integral (PI) and PID controllers that need only parameters obtained from the plant step response, the hardware implementation is not presented. Other works present web-based solution, for example, Colak et al [8] developed an advanced learning laboratory (NeTRed-LAB) for a DC motor that will allow students to operate real-world experiment on Internet. Albino-Mendez et al developed a free control Web-based tool; the tool covered basic and advanced operations allowing to work with both continuous and discrete-time system.…”
Section: Introductionmentioning
confidence: 98%
“…They concluded that the simulator is used to teach the power flow of the power system in undergraduate courses. Colak et al [12] developed a web-based laboratory for DC motors experiments in order to improve learning abilities of students and researchers in real-world applications on the Internet. Uyaroglu and Varan [13] analyzed a power system using MATLAB web figure control tool through web platform for teaching the relations between chaotic nonlinear dynamics and power system stability phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Bugüne kadar mühendislik eğitimine yönelik birçok arayüz çalışması gerçekleştirilmekle birlikte özellikle son yıllarda web tabanlı eğitim arayüz çalışmaları yaygınlaşmaktadır [5,10]. Bu çalışmalardan biri Erdem ve arkadaşları tarafından sayısal haberleşme eğitimi amaçlı gerçekleştirilen web tabanlı kullanıcı arayüzüdür.…”
Section: Gi̇ri̇ş (Introduction)unclassified